2017
DOI: 10.1039/c7cc01796k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 uptake by intramolecular proton transfer reactions in amino-functionalized pyridine-based ILs

Abstract: This work presents a new strategy for the promotion of CO uptake by an intramolecular proton transfer reaction in amino functionalized hydroxypyridine based anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…[11] As shown in Figure 1a (Figure 1b). The multi-site interactions between [IDA] and CO2 were further verified by FT-IR and 13 C NMR spectra (Figures 1c and 1d). In the IR spectra, the peak attributable to N-H stretch disappeared and simultaneously, two new characteristic peaks were observed at 1630 and 1423 cm -1 attributable to NH-CO2 and O-CO2 interactions, respectively.…”
Section: High Capacity Of Comentioning
confidence: 64%
See 3 more Smart Citations
“…[11] As shown in Figure 1a (Figure 1b). The multi-site interactions between [IDA] and CO2 were further verified by FT-IR and 13 C NMR spectra (Figures 1c and 1d). In the IR spectra, the peak attributable to N-H stretch disappeared and simultaneously, two new characteristic peaks were observed at 1630 and 1423 cm -1 attributable to NH-CO2 and O-CO2 interactions, respectively.…”
Section: High Capacity Of Comentioning
confidence: 64%
“…Proposed reaction between the first TSIL [apbim][BF4] and CO2. [6] Smart strategies including basicity tuning/dual tuning methods, [8,9] multi-site cooperative interactions, [10][11][12] and intramolecular hydrogen bonding/intra-molecular proton transfer [13,14] has been employed into ILs for CO2 capture. For examples, Dai et al [8] investigated the relationship between the enthalpy of CO2 absorption and the pKa value in a series of non-amino functionalized ILs and concluded that it is possible to achieve both efficient CO2 uptake and energy-saving release by simply tuning the basicity of the anion of IL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9] In light of the reaction mechanism of CO 2 in alkanolamine solutions and the outstanding properties of ILs, Davis et al 10 rst reported imidazolium ILs with amino-graed cation for the chemical absorption of CO 2 . Since the anion plays a key role in carbon capture, worldwide researchers have developed many kinds of task-specied ILs with the functionalized anions such as amino acids, [11][12][13][14] azolates, [15][16][17][18][19][20] phenolates, 7,[21][22][23] and acetate. 24 Compared with conventional ILs, these anion-functionalized ILs typically have high CO 2 absorption capacity and selectivity.…”
Section: Introductionmentioning
confidence: 99%